Pengaruh Rasio Keuangan Terhadap Nilai Perusahaan Industri Dasar dan Kimia Yang Terdaftar di Bursa Efek Indonesia - Azzahra, Fatimah; Hakip Nurdiansyah, Dian; Nurhanifah, Afifa (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to evaluate the impact of liquidity, profitability, activity, and solvency ratios on firm value in the basic and chemical industry sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 period. The independent variables used include Current Ratio (CR) to measure liquidity, Return On Assets (ROA) to measure profitability, Debt to Equity Ratio (DER) to measure solvency, and Fixed Asset Turnover (FAT) to measure activity. Meanwhile, the dependent variable analyzed is Market Capitalization (Market Cap) as a representation of firm value. This study uses a quantitative approach with a population of 66 companies and a sample of 46 companies selected through purposive sampling technique. Data analysis was carried out with logarithmic transformation base 10 (log10) and classical assumption testing, as well as using multiple linear regression analysis, t test, and F test. The results show that individually, ROA and FAT variables have a significant influence on Market Cap, while CR and DER show no significant influence. Overall, the four independent variables have a significant influence on Market Cap. This study provides an understanding of the factors that affect the value of companies in the basic and chemical industry sector, and provides implications for companies in managing financial performance and attracting investor interest.